Relative biological effectiveness of carbon ions for tumor control, acute skin damage and late radiation-induced fibrosis in a mouse model. (21st October 2015) - Sørensen, Brita S.; Horsman, Michael R.; Alsner, Jan; Overgaard, Jens; Durante, Marco; Scholz, Michael; Friedrich, Thomas; Bassler, Niels
ABSTRACT: Background. The aim of the present study was to compare the biological effectiveness of carbon ions relative to x-rays between tumor control, acute skin reaction and late RIF of CDF1 mice. Material and methods. CDF1 mice with a C3H mouse mammary carcinoma implanted subcutaneously on the foot of the right hind limb were irradiated with single fractions of either photons, or 12 C ions using a 30-mm spread-out Bragg peak. The endpoint of the study was local control (no tumor recurrence within 90 days). For the acute skin reaction, non-tumor bearing CDF1 mice were irradiated with a comparable radiation scheme, and monitored for acute skin damage between Day 7 and 40. Late RIF was assessed in the irradiated mice. Results. The TCD50 (dose producing tumor control in 50% of mice) values with 95% confidence interval were 29.7 (25.4–34.8) Gy for C ions and 43.9 (39.2–49.2) Gy for photons, with a corresponding Relative biological effectiveness (RBE) value of 1.48 (1.28–1.72). For acute skin damage the MDD50 (dose to produce moist desquamation in 50% of mice) values with 95% confidence interval were 26.3 (23.0–30.1) Gy for C ions and 35.8 (32.9–39.0) Gy for photons, resulting in a RBE of 1.36 (1.20–1.54). For late radiation-induced fibrosis the FD50 (dose to produce severe fibrosis in 50% of mice) values with 95% confidence interval were 26.5 (23.1–30.3) Gy for carbon ions and 39.8 (37.8–41.8) Gy for photons, with a RBE of 1.50 (1.33–1.69). Conclusion. The observed RBE values were very similar for tumor response, acute skin damage and late RIF when irradiated with large doses of high- linear energy transfer (LET) carbon ions. This study adds information to the variation in biological effectiveness in different tumor and normal tissue models.